Reduced model of plasma evolution in hydrogen discharge capillary plasmas - Boyle, GJ; Thevenet, M; Chappell, J; Garland, JM; Loisch, G; Osterhoff, J; D'Arcy, R (American Physical Society, 2021)
A model describing the evolution of the average plasma temperature inside a discharge capillary device including Ohmic heating, heat loss to the capillary wall, and ionization and recombination effects is developed. Key to this approach is an analytic quasistatic description of the radial temperature variation which, under local thermal equilibrium conditions, allows the radial behavior of both the plasma temperature and the electron density to be specified directly from the average temperature evolution. In this way, the standard set of coupled partial differential equations for magnetohydrodynamic (MHD) simulations is replaced by a single ordinary differential equation, with a corresponding gain in simplicity and computational efficiency. The on-axis plasma temperature and electron density calculations are benchmarked against existing one-dimensional MHD simulations for hydrogen plasmas under a range of discharge conditions and initial gas pressures, and good agreement is demonstrated. The success of this simple model indicates that it can serve as a quick and easy tool for evaluating the plasma conditions in discharge capillary devices, particularly for computationally expensive applications such as simulating long-term plasma evolution, performing detailed input parameter scans, or for optimization using machine-learning techniques.